2007
DOI: 10.1515/cclm.2007.321
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and growth factors in mostly atherosclerotic patients on hemodialysis determined by biochip array technology

Abstract: Plasma concentrations of some cytokines and growth factors could serve as useful diagnostic and prognostic parameters for patients with CRF on HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…41,42 We found that hemodialysis increased the concentrations of these cytokines and chemokines, consistent with previously published reports by our laboratory and others. 6,7 That bradykinin B 2 receptor blockade attenuated the rise in MCP-1 after hemodialysis concurs with data from cell culture studies.…”
Section: Discussionsupporting
confidence: 91%
“…41,42 We found that hemodialysis increased the concentrations of these cytokines and chemokines, consistent with previously published reports by our laboratory and others. 6,7 That bradykinin B 2 receptor blockade attenuated the rise in MCP-1 after hemodialysis concurs with data from cell culture studies.…”
Section: Discussionsupporting
confidence: 91%
“…It is well documented that the levels of several inflammatory cytokines were higher in CRF patients compared with control subjects, such as TNF-α, IL-6, IL-10, and MCP-1 5557 . Similarly, our data indicated that the levels of these cytokines were significantly increased compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF was initially thought to be an endothelial cell-specific mitogen that induces endothelial cell proliferation, but several studies have shown that VEGF may also contribute to the proliferation of vascular smooth muscle cells (35,36). Recent reports have demonstrated an association between elevated serum VEGF concentration and atherosclerosis (37,38). We have observed in this study that, like those of EMPs, VEGF values were markedly higher in uremic patients than in healthy subjects, and they were significantly higher in HD than in PD and CKD-NonD groups.…”
Section: Discussionmentioning
confidence: 99%